PREFERENSI PEGAWAI UIN-SU DALAM MENABUNG DI BANK SYARIAH - Ilhamy, Muhammad Latief (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2015)
This research aims to know the: (1) partially there was significant influence between the religious factor, economic interests and against the preference of employees of UIN-SU in saving in Islamic banks, and (2) simultaneous significant influence among religious factors, economic interests and against the preference of employees of UIN-SU in saving in the Islamic bank. This research uses a quantitative research method. A quantitative approach is an approach that emphasizes on testing theories or hypotheses through measurements of the variables research in numbers and perform data analysis with statistical procedures. The research design used the design quantitative research using multiple linear regression analysis technique is supported by a test model and statistical tests. This paper give For variables of interest and economic variables have no significant influence on the trend of saving.